قياس أثر معايير الاستثمارالاسلامي في البنك العربي الاسلامي الدولي في الأردن للمدة (2004 – 2013) - اخلاص باقر النجار (مجلة الغري للعلوم الاقتصادية والادارية)
المستخلص ينظر الى الإستثمار الإسلامي على انه اعمار الأرض وتنميتها واستثمار مواردها الإستثمار الأمثل بدافع العبادة في استثمار الأموال وتحريكها في مجالات استثمارية مختلفة تخلو من النواهي الشرعية كالربا والغش والغرر ، وحفظا للأموال وتحقيقاً للربح وتقليلاً للمخاطر ، والاستثمار ليس هو الربح انما هو وسيلة لتحقيق الربح ، فكل وجوه الاستثمار مباحة ما لم يرد فيه نص يحرمه ، ويمثل الإلزام بأن يغطي الاستثمار الأنشطة الاقتصادية الضرورية للمجتمع لتحقيق التنمية كأحد ضوابط المنهج الإسلامي ، أي الإلزام بتغطية كل الأنشطة الإقتصادية والإجتماعية وهناك عدد من المعايير التي تحكم الاستثمار الاسلامي لتحقيق الاهداف المرجوة منه ، وهي اعتبار ان الإنسان خليفة الله تعالى في الأرض ، وبما ان الإقتصاد الإسلامي يرتبط بالعقيدة وان الفرد عند قيامه بالنشاط الاقتصادي يُعدُّ عابداً ومتعبداً ، فإن الإستثمار وهو من أهم الأنشطة الإقتصادية يقوم على جوانب عقائدية ، وتتفق جميع الأنشطة الإقتصادية على استثمار الموارد المالية ووجوب تنميتها من أجل الإستفادة منها في خلق المنفعة أو زيادتها . Absract Seen Islamic investment as a reconstruction of the land and development and investment of resources the best investment out of worship in invest the money and moved in different investment areas devoid of prohibitions legitimacy such as usary , fraud and hazard , and to preserve the money and in order to achieve profit and minimize risk, and investment is not profit but it is a way to make a profit , all the faces Investment shall be permitted as provided deprive did not want it, and represents the obligation to cover the investment necessary economic activities of the community to achieve development as one controls the Islamic approach, any obligation to cover all economic and social activities, and there are a number of criteria that Islamic investment control to achieve the desired goals, which is regarded as the man successor God in the land, including the Islamic economy is linked to faith and the individual when resurrection of economic activity is the worshiper and the worshiped, the investment is one of the most important economic activities based on the ideological aspects, and consistent all economic activities on the investment of financial resources and the need to develop in order to make use of them in the creation of benefit or increased